FUTURE YOUTH, POSSIBILITIES AND ACHIEVEMENTS OF NEW UZBEKISTAN - Turdibekova Charos (Social science and innovation, 2024)
This article talks about the role of the neighborhood institute in the implementation of the state policy on youth in Uzbekistan during the years of independence and the achievements of our youth